Coping with weight stigma: Validation of the Persian brief coping responses inventory with Iranian adolescents sample - Kargari Padar, Leila; Asgharnejad Farid, Ali Asghar; Fathali Lavasani, Fahimeh; Farahani, Hojjatollah; Gharaei, Banafsheh (Frontiers in Psychology, 2022)
Individuals who are overweight or obese encounter frequent weight-related stigma experiences, which are associated with negative health outcomes. In this regard, the Brief Coping Responses Inventory (BCRI) was developed as a measure of core coping responses to weight stigma, with ten items loading on two subscales of reappraisal and Disengagement coping. The current study aimed to examine the psychometric properties of the Persian BCRI with 253 Iranian school-attending youth ( Mage = 15.38, SD ± .50; 53% female) who had BMI score over 30. The results of the confirmatory factor analysis supported the originally proposed two-factor model (RMSEA = .028; CFI = .996; TLI = .994), which yielded acceptable internal consistency based on various reliability measures such as Cronbach's alpha coefficients (.79 and .88 for reappraisal and disengagement factors, respectively) and demonstrated the expected convergent and divergent associations with external correlates of interest (e.g., anxiety, depression, and body dissatisfaction scores). This study was also the first one worldwide to examine and report that the originally proposed two-factor model of the BCRI is invariant across gender groups, which allows for examining mean differences in BCRI scores across gender groups. Overall, our results indicated that the BCRI is a valid and reliable measure with a solid factor structure, which could be used to examine the coping reactions to weigh related stigma experiences among youth samples in Iran. Our results may encourage future studies on the psychometrics of the BCRI with other Iranian samples (e.g., university students, community, and clinical samples).